Female athlete health domains: a supplement to the International Olympic Committee consensus statement on methods for recording and reporting epidemiological data on injury and illness in sport - Moore, I. S.; Crossley, K. M.; Bo, K.; Mountjoy, M.; Ackerman, K. E.; da Silva, J. A.; Borgen, J. S.; Brown, W. J.; Bolling, C.; Clarsen, B.; Derman, W.; Dijkstra, P.; et al. (British Journal of Sports Medicine, 2023)
The IOC made recommendations for recording and reporting epidemiological data on injuries and illness in sports in 2020, but with little, if any, focus on female athletes. Therefore, the aims of this supplement to the IOC consensus statement are to (i) propose a taxonomy for categorisation of female athlete health problems across the lifespan; (ii) make recommendations for data capture to inform consistent recording and reporting of symptoms, injuries, illnesses and other health outcomes in sports injury epidemiology and (iii) make recommendations for specifications when applying the Strengthening the Reporting of Observational Studies in Epidemiology-Sport Injury and Illness Surveillance (STROBE-SIIS) to female athlete health data.